Upregulated lncRNA UCA1 inhibits trophoblast cell invasion and proliferation by downregulating JAK2. Issue 10 (17th February 2020) - Liu, Jie; Luo, Chengyan; Zhang, Chu; Cai, Qian; Lin, Jihui; Zhu, Tong; Huang, Xiaojie
Abstract: Numerous studies have suggested that urothelial cancer‐associated 1 (UCA1) acts as a suppressor gene affecting cell proliferation and migration. However, the biological role and the potential mechanism of UCA1 in the progression of pre‐eclampsia (PE) remains unclear. The UCA1 level was markedly upregulated in PE pregnancies relative to non‐PE ones in GSE75010 and tissues. A higher body mass index (BMI), maximum systolic blood pressure (BP), and maximum diastolic BP were observed in PE pregnancies, whereas the newborn weight z ‐score was lower compared with those of non‐PE pregnancies. Knockdown of UCA1 accelerated the proliferative migratory abilities and cell cycle progression, but inhibited apoptosis of HTR‐8/SVneo and JAR cells. Then, we found that Janus kinases 2 (JAK2) was negatively correlated with UCA1. In addition, JAK2 was downregulated in the placenta of PE pregnancies and was negatively regulated by UCA1. UCA1 was mainly enriched in the nucleus. Knockdown of UCA1 reduced the occupancies of the enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) and H3K27me3 on the Janus kinase 2 (JAK2) promoter regions. Finally, rescue experiments found that transfection of short‐hairpin JAK2 attenuated proliferative and migratory abilities of trophoblasts, which were partially reversed after UCA1 knockdown. In short, UCA1 is upregulated in the trophocytes of PE pregnancies and accelerates trophoblast cell invasion and proliferation by downregulating JAK2.